2017
DOI: 10.1039/c7dt03427j
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature growth of gallium oxide thin films via plasma enhanced atomic layer deposition

Abstract: Herein we describe an efficient low temperature (60-160 °C) plasma enhanced atomic layer deposition (PEALD) process for gallium oxide (GaO) thin films using hexakis(dimethylamido)digallium [Ga(NMe)] with oxygen (O) plasma on Si(100). The use of O plasma was found to have a significant improvement on the growth rate and deposition temperature when compared to former GaO processes. The process yielded the second highest growth rates (1.5 Å per cycle) in terms of GaO ALD and the lowest temperature to date for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
61
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 89 publications
8
61
0
Order By: Relevance
“…Notably, all previous reports using 1 has resulted in amorphous films at all deposition temperatures. 19,21,22 We show that 1 displayed self-limiting behaviour in a temperature range from 130-250 1C on Si (100). Deposition of GaN on 4H-SiC(0001) rendered epitaxial films with near stochiometric composition and very low impurity levels of carbon and oxygen.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Notably, all previous reports using 1 has resulted in amorphous films at all deposition temperatures. 19,21,22 We show that 1 displayed self-limiting behaviour in a temperature range from 130-250 1C on Si (100). Deposition of GaN on 4H-SiC(0001) rendered epitaxial films with near stochiometric composition and very low impurity levels of carbon and oxygen.…”
Section: Introductionmentioning
confidence: 79%
“…Tris(dimethylamido)gallium(III) dimer 1 has been previously used in ALD studies, [19][20][21] however its thermal properties have not been reported as far as we know. Thermogravimetric analysis (TGA) showed 1 evaporated in a single step from 140-230 1C, with only 5% of residual mass (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, several studies have also shown that the direct bandgap (located at Γ) is only 0.04 eV larger, with a bandgap of 4.88 eV [42][43][44] . The majority of papers available in which UV-Vis spectroscopy has been used for the study of Ga2O3 films use the direct bandgap assumption when calculating Tauc plots 1,4,26,28,30,32,45 , i.e: ℎ ∝ (ℎ − ) 1 2 ⁄ where is the optical absorption coefficient, ℎ is the photon energy and is the optical bandgap. Thus a plot of ( ℎ ) 2 against ℎ can be used to extract .…”
Section: Figure 3: Cross-sectional Adf-stem Images Of the Ga2o3 Filmsmentioning
confidence: 99%
“…Notably, all previous reports using 1 has resulted in amorphous films at all deposition temperatures. 19,21,22 We show that 1 displayed self-limiting behaviour in a temperature range from 130-250  C on Si(100). Deposition of GaN on 4H-SiC(0001) rendered epitaxial films with near stochiometric composition and very low impurity levels of carbon and oxygen.…”
Section: Introductionmentioning
confidence: 80%
“…Herein, we report low temperature deposition of GaN using tris(dimethylamido)gallium(III), (Ga(N(CH3)2)3 1, with NH3 plasma by ALD. Precursor 1 has been previously used for ALD of Ga2O3 19,20 and Ga2S3 21 and CVD of GaN 22 , but not for ALD of GaN. Notably, all previous reports using 1 has resulted in amorphous films at all deposition temperatures.…”
Section: Introductionmentioning
confidence: 99%